2008
DOI: 10.1155/2009/361490
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amino Acid Analogues of 5H‐Dibenz[b,f]azepine and Evaluation of their Radical Scavenging Activity

Abstract: A method for the synthesis of tyrosine, phenyl alanine, hydroxy proline and threonine free amino acid analogues of 5H-dibenz[b,f]azepine is proposed. 5H-dibenz[b,f]azepine was prepared by known method. The key intermediate 3-chloro-1-(5H-dibenz[b,f]azepine-5-yl)propan-1-one was obtained byN-acylation of 5H-dibenz[b,f]azepine with 3-chloro propionyl chloride. Further coupling of respective free amino acid to produce 2-(3-(5H-dibenz[b,f]azepine-5-yl)-3-oxopropylamino)3-(4 hydroxyphenyl) propanoic acid, 2-(3-(5H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This may be due to the absence of a hydroxyl group. Among the synthesised conjugates, 1-(3-(5H-dibenz[ b , f ]azepine-5-yl)-3-oxopropyl)-3hydroxypyrolidine-2-carboxylic acid showed the highest activity with an IC 50 value of 4.1 ± 0.87 µM/mL, which might be due to the presence of a hydroxyl group of Hyp [ 111 ].…”
Section: Conjugated or Hybrid Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the absence of a hydroxyl group. Among the synthesised conjugates, 1-(3-(5H-dibenz[ b , f ]azepine-5-yl)-3-oxopropyl)-3hydroxypyrolidine-2-carboxylic acid showed the highest activity with an IC 50 value of 4.1 ± 0.87 µM/mL, which might be due to the presence of a hydroxyl group of Hyp [ 111 ].…”
Section: Conjugated or Hybrid Moleculesmentioning
confidence: 99%
“…The conjugation of Hyp (IC 50 = 4.1 ± 0.87 µM/mL) showed superior activity due to the presence of -OH group on pyrrolidine ring. Finally, the authors concluded that Hyp conjugate reported the highest activity among the synthesised derivatives [ 115 ].…”
Section: Conjugated or Hybrid Moleculesmentioning
confidence: 99%
“…[20] The scientific studies focused on amino acids and some of their derivatives revealed high antioxidant activity particularly their potential radical scavenging activities associated with cancer cells. [21] Glutathione synthesized in cells from its constituent amino acids (glutamate-cysteine-glycine) has antioxidant properties and capable of preventing damage to important cellular components caused by reactive oxygen species such as free radicals, peroxides, lipid peroxides, and heavy metals. [22] In addition, N,N'-dicyclohexylcarbodiimide (DCC) is a widely used reagent as a powerful dehydrating agent in the coupling of amino acids for the peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature amino acids and some of their derivatives were also found to have antioxidant activity [20] . The scientific studies focused on amino acids and some of their derivatives revealed high antioxidant activity particularly their potential radical scavenging activities associated with cancer cells [21] …”
Section: Introductionmentioning
confidence: 99%
“…An effective anticonvulsant drug, 5H-dibenzo[b,f]azepine-5-carboxamide, was first synthesized by Schindler [13] in 1960 and since then it has become the most frequently prescribed first-line drug for the treatment of epilepsy. In addition, dibenzo[b,f]azepine derivatives are useful due to their antimicrobial [14], antioxidant [15,16], and antitubercular [17] activities.…”
Section: Introductionmentioning
confidence: 99%